Risk and Protective Factors in Children Bullying Perpetration: Application of the Multiple Disadvantage Model - Cheng, Tyrone C. (Journal of interpersonal violence, 2025)
This secondary study examined bullying perpetration’s relationships with social disorganization, social structural factors, social relationships, mental health, and access to health insurance and care. A sample of 30,173 children age 6 to 17 years was extracted from the 2021 National Survey of Children’s Health for secondary data analysis. Logistic regression results demonstrated that these children’s likelihood of bullying perpetration was positively associated with racial discrimination, child age 6 to 10 years, child age 11 to 13 years, parent education level, employed parent, neighbor support, family violence, difficulty parenting the child, child difficulty with peers, child behavioral/conduct problems, family substance use problem, and child receipt of mental health services; such likelihood also had negative associations with safe neighborhood, Black, Asian, other non-Hispanic ethnic minority, parent age, and family cohesiveness. Implications included interventions to promote awareness of racial discrimination for families as well as bully prevention programs in schools and communities.